WHISTLEBLOWING EFFECTIVENESS: THE ROLE OF ETHICAL CLIMATE AND REGULATORY STRENGTH IN SHAPING THE WHISTLEBLOWING INDEX - Muhammad Syahmi Adli Roslan; Muhammad Hariz Hamid; Roshima Said; Fazlida Mohd Razali, (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME'S (AIJBES), 2025)
Whistleblowing serves as a critical mechanism for promoting corporate transparency, ethical governance, and accountability. While prior studies have examined the individual influence of organisational ethics and regulatory frameworks on whistleblowing practices, limited research has explored their interactive effects on whistleblowing effectiveness. This study addresses that gap by proposing a conceptual framework that integrates ethical climate as an internal organisational factor and regulatory strength as an external moderating force in shaping the whistleblowing index, a structured measure of whistleblowing effectiveness. Grounded in institutional theory, this study employs a narrative review methodology to synthesise interdisciplinary literature from business ethics, corporate governance, and regulatory studies. Findings indicate that a strong ethical climate fosters employee willingness to report misconduct, while robust regulatory mechanisms enhance the safety and legitimacy of such disclosures. The interaction between these dimensions is essential for improving whistleblowing outcomes, particularly in mitigating barriers such as fear of retaliation and weak legal protection. The proposed framework offers theoretical contributions by unifying organisational norms and institutional pressures, and practical implications for corporate leaders and policymakers. It underscores the need for organisations to align ethical cultures with legal safeguards to foster an environment conducive to whistleblowing. The study concludes by calling for empirical research to validate the framework across varied cultural and sectoral contexts, thereby strengthening whistleblower protection and enhancing corporate integrity.